The Relationship Between Working Posture and Musculoskeletal Disorders in Waste Pickers at Blondo Landfill - Heryanda, Annisa Putri; Lestari, Sri (Journal of Public Health for Tropical and Coastal Region, 2024)
Abstract Background: Blondo landfill serves as a final processing site for waste and also a source of livelihood for scavengers. Scavengers are workers who are at risk of musculoskeletal disoders (MSDs) complaints due to heavy, repetitive physical work and poor work postures due to bending. During waste collection and sorting, waste pickers perform repetitive movements with non-ergonomic postures, away from the ideal body position. Based on data from Puskesmas Bawen, 45% of 73 waste pickers experienced muscle and joint pain. The purpose of this study was to determine the relationship between working posture and complaints of musculoskeletal disorders.Methods: This study was an observational analytic research in a cross sectional design. The population in this study were Blondo landfill waste pickers. The subjects were 65 waste pickers who were chosen through purposive sampling technique. Data collection was conducted through interviews using the Nordic Body Map questionnaire, digital camera and REBA (Rapid Entire Body Assessment) sheet. Data analysis were conducted using Spearman rank tests.Results: The results showed that of the 65 waste pickers, the majority were female (53.3%), aged > 35 years (93.8%), had a working period of more than 5 years (61.5%), and normal nutritional status (56.9%). Scavengers who have moderate risk work posture (81.5%) and moderate musculoskeletal disorders (84.6%). There was a positive correlation between working posture and MSDs with a moderate level (ρ=0.593; p=0.0001).Conclusion: Work postures that are formed away from the body's gravity which if done continuously and for a long period of time among waste pickers resulted in musculoskeletal disorders.